Hemangiopericytoma of the Breast: A Case Report and a Review of the Literature - Georgios Koukourakis; Evagelos Filopoulos; Kasiani Kapatou; Georgios Zacharias (Case Reports in Oncological Medicine)
Introduction. Sarcomas of the breast are rare and hemangiopericytoma (HPC) of the breast is even rarer. Case Report. We report a case of a 43-year-old woman who presented with a 4 cm mass in her right breast. Her family history was positive for breast cancer. A fine needle aspiration indicated a malignant vascular tumor. An excision biopsy and frozen section analysis confirmed the presence of an encapsulated mesenchymal tumor. Its morphology and immunohistochemical marker profile were characteristic for a malignant hemangiopericytoma. Thus, she underwent a tumor excision without an axilla sampling. Approximately one year after the surgery the patient is well without local recurrence or metastasis disease to be observed. We also reviewed the literature and discuss the treatment options, characteristics, and immunophenotype of HPC. Conclusions. The accurate diagnosis of HPC depends on the appropriate histological and immunohistochemical examination. Surgical resection is the treatment of choice and due to scarcity of cases and unpredictable biological behavior of these tumors long term follow-up may be warranted.